Работы украинско-российской Восточно-Крымской экспедиции - Гаврилюк, Н.А.; Масленников, А.А.; Винокуров, Н.И.; Хршановский, В.А.; Зубарев, В.Г.; Ермолин, А.Л. (Археологічні дослідження в Україні, 2010)
Results of the field work of the united Ukrainian-Russian Eastern-Crimean Expedition at 10 Ancient sites are summarized.